Prevalence of new born care practice and its associated factors among women who gave birth in the last one year in Adigrattown, Adigrat, Tigray, Ethiopia, 2018/19 - Teferi, Marzeneb; Teferi, Molla; Ayalew, Assefa (Archives of Community Medicine and Public Health, 2020)
Background: Newborn care is a set of comprehensive recommendations designed by the World Health Organization to improve health of the newborn through intervention before conception, during pregnancy, soon after birth and during the postnatal period. Lack of effective use of the recommendations of the health care providers may lead to increased neonatal mortality. The first hours are crucial because multiple organ system is making the transition from intrauterine to extra uterine functions. The care given immediately after birth is simple but important. Objective: To assess practice of new born care and its associated factors among women who gave birth in the last 12 months in Adigrat Town, Adigrat ,Tigray ,Ethiopia, 2019. Methods and materials: Community based Cross-sectional study was conducted from Nov 2018 to January 2019 in Adigrat Town. We used a Systematic random sampling technique and 389 were selected for the study area. 35 items standard questionnaires were used and three grade twelve students were employee to collect the data. Data was checked for completeness, consistency, coded and entered in to SPSS version 22 for analysis and we got ethical clearance from the Adigrat University College of medical health science. Result: A total of 389 women responded to the questionnaire and its response rate was 100%. And the mean age and standard deviation was 27 (+SD 5.9) years. Majority 319(82%)of them were married.39.8 % of mothers knew the normal (8-10) breastfeeding practice and 96.9% mothers initiated breast feeding with in the first one hour. 96.1 % used new blade to cut the umbilical cord and only 54.2% correctly reported that umbilical stump should be uncovered. 96.6% applied substances identified by the mothers were butter.55% of mothers reported that baby should be bath after 24 hours of delivery. the modes of keeping the baby warmed by cloth before the expulsion of the placenta was 89.5%. Conclusion and recommendation: -Marital status, gravidity and parity have significant association with newborn care. The Town health office should use multi-gravida mothers to share their experience on newborn care practice for primi-gradiva as health development army.